The Application of English Conversation Pocket Book in Teaching Students' Speaking Skill ( A Descriptive Qualitative Study at MTS ja-alhaq Bengkulu City in the Academic Year 2021/2022) - Nurmela; Rizal, Syamsul; Utami, Valisneria (JPT : Jurnal Pendidikan Tematik, 2022)
Speaking is the most important skill among the four language skill in order to communicate well in this globalized world, especially speaking in English. The data collected by the researcher shows that there are some problems with learning speaking skills. Some of these problems are, students lack confidences in speaking English, students have difficulty in pronouncing English correctly, students are lazy to memorize English vocabulary, and students are less interested in learning English. learn English. With the problems faced by these students, in 2020 the MTs ja-alhaq school launched a pocket book for foreign language conversations which was used as an aid medium in learning students' speaking skills. This conversation pocket book is used during the foreign language development institute program. Foreign language development institutes are programs that study foreign languages. The result from this study is the application of an English conversation pocket book in teaching speaking skills in class VIII MTs Ja-Alhaq the English conversation pocket book has a positive response because it really help the teacher and students in the process of leaning a foreign language, especially English, even though the teacher has obstacles in the learning process.